Management of Religious Tourism Objects Based on Local Wisdom - Joorie M. Ruru; Very Y. Londa; Novie R. A. Palar; Welson Y. Rompas (Journal La Sociale, 2022)
The government has made tourism as one of the leading sectors in development. So that it makes all levels of government seem to be competing to develop tourist attractions. Tourist objects that have good selling points and are difficult to imitate by other regions are religious tourism objects and based on local wisdom. This research was conducted using a qualitative design to explore the management of religious tourism objects and based on local wisdom in North Sulawesi Province. Research data were collected through direct interviews, using google forms and utilizing google scholars and researchgate. Data analysis was carried out inductively and validity strengthening through focus group discussions. Research findings North Sulawesi province has tourism objects that can be developed through religious concepts and local wisdom. However, it requires improving the management of attractions/attractions, tourism marketing, infrastructure and accessibility, tourism facilities/facilities, managing resources, character and culture as well as community participation.